(untitled) (International Journal of Physiotherapy, 2015)
Background: The aim of this report was to determine the effects of electrical stimulation and laser radiation on non-small lung cancer (A549) and Chinese Hamster Ovary cell line (CHO AA8). Furthermore, we also analyzed viability and size of the extracellular spaces in CHO AA8 and A549 cells. Methods: In order to evaluate the cell viability Tali® Image-Based Cytometer was used. The material (non-small lung cancer cell – A549 and Chinese Hamster Ovary – CHO AA8) was evaluated by the light and confocal fluorescence microscope. Results: The data demonstrated that exposure to both electrical stimulation and laser radiation for 3 and 5 minutes showed non statistical differences in the percentage of live cells. The morphological abnormalities and microfilaments reorganization indicated induction non apoptotic type of cell death such as mitotic catastrophe. Moreover, CHO AA8 as non-cancerous cells exhibited lower sensitivity for laser and electrical stimulation in comparison to A549 cell line. Conclusions: Our results confirmed contraindicated the use of these methods, especially due to an increase of the risk of metastasis. Moreover, our study suggests that the laser radiation and electrical stimulation may have limited applications in the cancer patients and that choice of these treatment methods should be used in carefully selected patients.